Utilization & Quality of Information System for Administration Services Based on ICT In Patehan, Kraton, Yogyakarta - Rohmah, Amandita 'Ainur; Rachmawati, Rini (Universitas Pendidikan Indonesia, 2019)
Development of technology and application of e-government at city, sub-district, and village become the factor of emergence of Information and Communication Technology-based information service system innovation. Yogyakarta has implemented e-government as one of the strategies used to achieve the slogan of Yogyakarta Smart City. One of the areas that have implemented the concept is Patehan, Kraton, Yogyakarta. This research aims to describe the system of online administrative services, identify of utilization by the community, and measure the quality of its services. The research method used was qualitative and quantitative methods. Data collected are primary data and secondary data with analytical technique used is descriptive qualitative and quantitative. Based on the results of the research can be seen that the administrative service system in Patehan (SiWarga Patehan) is a system made by citizens, for citizens, and from citizens to take care of online certificate from RT, RW until the village that serve as one alternative for the community has high mobility. Based on 60 respondents, it can be concluded that the administrative system of SiWarga Patehan included into the category of good with the service index of 79.97.